2006
DOI: 10.1039/b606073k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced solid-state electrochemiluminescence of CdS nanocrystals composited with carbon nanotubes in H2O2 solution

Abstract: CdS nanoparticles composited with carbon nanotubes not only enhances their electrochemiluminescent intensity but also decreases their ECL starting potential; such a property would promote the application of quantum dots in fabricating sensors for chemical and biochemical analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
103
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(104 citation statements)
references
References 16 publications
1
103
0
Order By: Relevance
“…These two ECL peaks resulted from the reaction between H 2 O 2 and individual reduced NC species (À1.30 V) and the reaction between H 2 O 2 and assembly of CdS reduced NC species (À1.44 V). [6,10,14] However, in the ECL of MWCNT-CdS modified PIGE, two ECL peaks were observed at À1.02 V and À1.35 V (Fig. 3B curve b).…”
Section: Ecl and Electrochemical Behaviors Of Mwcnt-cds Ncs Modified mentioning
confidence: 99%
See 1 more Smart Citation
“…These two ECL peaks resulted from the reaction between H 2 O 2 and individual reduced NC species (À1.30 V) and the reaction between H 2 O 2 and assembly of CdS reduced NC species (À1.44 V). [6,10,14] However, in the ECL of MWCNT-CdS modified PIGE, two ECL peaks were observed at À1.02 V and À1.35 V (Fig. 3B curve b).…”
Section: Ecl and Electrochemical Behaviors Of Mwcnt-cds Ncs Modified mentioning
confidence: 99%
“…Our previous work showed that carbon nanotube (CNT) could not only enhance CdS NCs ECL intensity greatly but also decrease their ECL onset potential. [14] In that work, the CNT/CdS composite was obtained through the CdS NCs capped with thioglycolic acid attached on the surface of functional CNT under ultrasonication at a desired ratio. However, one of the limitations of such methodology is that it yields primarily unorganized, discrete one dimensional ''ball-and-stick'' structures, which are very difficult to organize into an ordered assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Their application in electrochemiluminescent (ECL) sensing has gained particular concern since the first ECL sensor based on CdSe QDs was reported in 2004 [3]. Owing to the low ECL intensity and high excited potential of QDs, new methods to decrease the excited potential and enhance ECL emission are urgently needed for the development of novel ECL sensors [4]. In view of the excellent electrocatalytic ability of carbon nanotubes (CNTs) [5], they have been used to reduce the injection barrier of electrons to the QDs for improving the ECL response [4] and constructing ECL immunosensors [6].…”
mentioning
confidence: 99%
“…Owing to the low ECL intensity and high excited potential of QDs, new methods to decrease the excited potential and enhance ECL emission are urgently needed for the development of novel ECL sensors [4]. In view of the excellent electrocatalytic ability of carbon nanotubes (CNTs) [5], they have been used to reduce the injection barrier of electrons to the QDs for improving the ECL response [4] and constructing ECL immunosensors [6]. This work examined the sensitizing effect of nitrogen-doped carbon nanotubes (NCNTs) to the ECL emission of CdSe QDs.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Nanotubes may be formed from a variety of materials including carbon, ceramics, metals and organic polymers. [6][7][8][9] The organic polymer nanotubes possess high resistance to chemical and structural imperfection and nice ability to form ordered films, and thus have attracted increasing interests in recent years.…”
Section: Introductionmentioning
confidence: 99%